Drug treatment of vestibular migraine (Research, Society and Development, 2021)
Vestibular migraine corresponds to one of the most frequent diagnoses in otoneurology. It is considered the most common cause of balance disorders. Its diagnosis is based on recurrent vestibular symptoms, history of migraine and association of migraine symptoms with vestibular symptoms over a period ranging from 5 minutes to 72 hours. The drug treatment of vestibular migraine aims to control the patient's symptoms in the acute phase, as well as in the prophylaxis of eventual crises. The present work is an integrative literature review, whose objective is to identify and describe the drug treatment of vestibular migraine, in order to control the patient's symptoms in the acute phase and in the prophylaxis of possible crises. The search was carried out in the electronic databases SCIELO, PUBMED and LILACS, including works published between 2016 and 2021, in Portuguese and English. The selection of studies, data extraction and validation were carried out independently by two authors, obtaining a sample of 14 articles. All research data were analyzed in Microsoft Excel and later the results were transformed into tables for a better interpretation of the information collected. It was found, through the analysis of the 14 articles, that 7 (50%) studies used treatment with antidepressants, beta-blockers and anticonvulsants concomitantly; 9 (64%) used propranolol with symptom improvement; 2 (14%) used botulinum toxin and only 1 (7%) used gentamicin injection. Thus, it was possible to systematically structure the drugs most used in prophylaxis and in the vestibular migraine crisis, laying the basis for a more adequate choice of the drug.